Alkali-Activated Binders From Waste Incinerator Bottom Ashes and Metakaolin Reinforced by Recycled Carbon Fiber Composites - Manzi, Stefania; Lancellotti, Isabella; Masi, Giulia; Saccani, Andrea (Frontiers in Materials, 2020)
In view of creating low-impact materials for the building industry, the fostering of alkali-activated binder gains high importance. Metakaolin can successfully be activated with alkalis at room temperature but the contemporary use of wastes to create mixed binders can further increase the derived environmental benefits. Bottom ashes deriving from the incineration of municipal solid wastes have been tentatively mixed in different amounts to develop matrix with acceptable mechanical properties, still to be cured at room temperature. Moreover, scraps deriving from the production of epoxy/carbon fibre composites are employed as a reinforcing phase. No chemical or physical treatments have been used to modify the epoxy/carbon fibre wastes, apart from size reduction, thus minimizing the overall economic and energy impact of the process. The workability, physical and mechanical properties, microstructure and porosity of the obtained materials are investigated. Up to a 50 weight % amount of municipal solid waste incineration bottom ashes can be mixed with metakaolin. Fibres still embedded in the epoxy matrix disclose a fair interaction with the matrix thus managing to increase flexural strength, toughness and dimensional stability without decreasing the compressive strength.